DISCURSOS Y PRÁCTICAS EN TORNO A LAS COMPETENCIAS EN EDUCACIÓN - Dra. Juana M. SANCHO (Fonseca, Journal of Communication, 2023)
In this paper, based on the knowledge elaborated through different research projects carried out in recent years, I first argue the difficulty of creating discourses and proposals from the field of education due, among other factors, to the scarcity of means and resources for educational research. Second, I refer to the social, political, economic, cultural and technological changes that have led to the emergence and expansion, especially from the business field, of the discourses on the importance and convenience of implementing competency-based teaching and learning processes